Emergency Department Physicians’ Knowledge of Synthetic Cannabinoids (Annals of Medical Research, 2021)
Aim: Substances containing synthetic cannabinoid are known with different names in various countries and abuse of these substances increase day by day. Different combinations of these substances make difficult to predict clinical effects. In this study, the aim is to evaluate the awareness of emergency department physicians on the clinical presentation of people using these substances.Materials and Methods: A questionnaire was applied to 100 physicians in emergency departments; the survey did not involve any scales but only contained the following three options: “Yes,” “No,” and “No idea.”Results: The average age of physicians was 34,5±6,8 and the average work experience in the emergency department was 6,4±5,2 years. The proportion of research assistants was 42%; 29% of the physicians were experts while the other 29% were practitioners. The rate of the physicians with true knowledge abouth varied clinical appearances of drug abuse was 68%. The percentage of physicians who had no idea about the variable contents of this substances was 44%. 80% of the physicians knew that it is necessary to report these cases as "Criminal cases."Conclusion: Due to the rapid increase in the use of substances containing synthetic cannabinoid, physicians should consider welcoming new information and improve their knowledge on these substances and their properties.Keywords: Substance Dependence; Hospital Emergency Service; Legal Medicine.